Pengaruh Hemoglobin, Lingkar Lengan Atas, Usia, dan Paritas Ibu terhadap Berat Lahir Bayi - Neki (Agribiohealth (Journal of Agriculture, Biology & Health Sciences), 2025)
Chronic energy deficiency and anemia during pregnancy remain public health problems that contribute to the incidence of low birth weight (LBW). Maternal factors such as hemoglobin level, mid–upper arm circumference (MUAC), maternal age, and parity are known to influence intrauterine nutrient supply. This study aimed to analyze the relationship between these maternal factors and neonatal birth weight. An analytical observational study with a cross-sectional design was conducted among 60 postpartum mothers who delivered live infants at Kasihan I Primary Health Center, Bantul Regency, from January to December 2024. Total sampling was applied. Data were obtained from medical records, including maternal hemoglobin levels, MUAC, age, parity, and neonatal birth weight. Data analysis consisted of univariate, bivariate, and multivariate regression analyses. The prevalence of low birth weight was 35%. MUAC showed a significant association with birth weight (p < 0.001) with a moderate correlation strength (R = 0.50). Each 1 cm increase in MUAC was associated with an increase of approximately 182 grams in neonatal birth weight. In contrast, maternal age, parity, and hemoglobin levels were not significantly associated with birth weight (p > 0.05). Maternal mid–upper arm circumference was identified as the most influential factor affecting neonatal birth weight.